2005
DOI: 10.1051/0004-6361:20053077
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Mn, Co and Eu in a sample of 20 F–G disk stars: the influence of hyperfine structure splitting

Abstract: We present Mn, Co and Eu abundances for a sample of 20 disk F and G dwarfs and subgiants with metallicities in the range −0.8 ≤ [Fe/H] ≤ +0.3. We investigate the influence of hyperfine structure (HFS) on the derived abundances of Mn and Co by using HFS data from different sources in the literature, as well as calculated HFS from interaction factors A and B. Eu abundances were obtained from spectral synthesis of one Eu  line that takes into account HFS from a series of recent laboratory measurements. For the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Intrinsic cosmic scatter can be the result of the heterogenous nature of the original interstellar medium from which each star was formed. However, all too often scatter arises from differences in the procedure used by different authors, which could involve parameters as divers as different line sets, atomic constants, h f s employed (del Peloso et al 2005), solar abundances as reference, atmosphere models, and spectrum synthesis codes. Table 6 shows that the difference between results obtained for Mn abundances by different authors for some stars can reach 0.50 dex, whereas for Cu and Zn this difference is smaller.…”
Section: Abundance Scattermentioning
confidence: 99%
“…Intrinsic cosmic scatter can be the result of the heterogenous nature of the original interstellar medium from which each star was formed. However, all too often scatter arises from differences in the procedure used by different authors, which could involve parameters as divers as different line sets, atomic constants, h f s employed (del Peloso et al 2005), solar abundances as reference, atmosphere models, and spectrum synthesis codes. Table 6 shows that the difference between results obtained for Mn abundances by different authors for some stars can reach 0.50 dex, whereas for Cu and Zn this difference is smaller.…”
Section: Abundance Scattermentioning
confidence: 99%
“…All fine-structure and hyperfine-structure components for the lines of Cu i, Mn i and Eu ii were explicitly included. The g f -values for Cu i are from Koch & Richter (1968), those for Mn i and Eu ii are from del Peloso et al (2005).…”
Section: Abundance Analysismentioning
confidence: 99%
“…In the framework of testing nucleosynthesis models, Ellison et al (2001) identified Co as a rewarding element to study galactic and stellar formation histories through the observed abundance trends (del Peloso et al 2005). For example, the agreement of the modeled time-dependent ejecta compositions and velocities with observed Type 1a supernovae spectra requires a substantial initial presence of Ni , Co , and Fe in the outer layers of the ejecta (Hillebrandt & Niemeyer 2000).…”
Section: Introductionmentioning
confidence: 99%